Recurrent Macroprolactinoma with Malignant Conversion to Carcinoma with Spinal Metastasis - Madeline Mori; Amanda Frugoli; Udesh Shah; Brad Barrows; Tricia Westhoff; David Westra (Case Reports in Endocrinology)
In contrast to pituitary adenomas, pituitary carcinomas represent a rare malignant neoplasm with a remarkable high mortality. Pituitary carcinomas can arise from any pituitary tumor cell line and are determined to be carcinomas when there is distant metastasis or central nervous system dissemination. In this case vignette, we describe a rare case of malignant prolactinoma with intraspinal metastasis, and we also provide a review of relevant literature and treatment.